Construction of Responsibility Character of Elementary School Students Through Karawo Local Wisdom Values - Hasan, Novita; Yunus, Rasid; Ahmad, Muchtar (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the use of local wisdom as a means of constructing the character of responsibility of elementary school students and the factors that hinder these efforts. Methodology: Using descriptive qualitative methods, data were collected through in-depth interviews, participatory observation, and documentation studies from various sources such as teachers, principals, parents, Karawo craftsmen, as well as traditional leaders, with purposive sampling techniques and data validity was maintained through triangulation of sources, techniques, and time. Main Findings: The research findings show that Karawo local wisdom is able to construct students' responsibility character through a learning process that emphasizes perseverance, thoroughness, and commitment in completing tasks. These values are integrated in various subjects, so students learn responsibility contextually and thoroughly. Embroidery activities encourage students to be disciplined, thorough, and consistent, while fostering a sense of responsibility for the preservation of local culture that they inherit and are proud of. Novelty/Originality of this study: The novelty of this study lies in the utilization of Karawo as a medium of character education. So far, Karawo has been seen more as an economic source, it has not been maximally utilized in the realm of education, especially for student character building